The failing heart: a bad case of the 'flu'. (5th February 2015) - Wilson, Julie; Akhtar, Mohammed Majid; Modi, Bhavik; Emmanuel, Julian
Abstract : A 24-year-old Nepali man presented to hospital with a short history of feeling unwell with a flu-like illness. He subsequently went into acute renal failure requiring several sessions of renal replacement therapy by haemofiltration. The underlying aetiology of his renal failure was unclear. His renal function recovered following haemofiltration and he was discharged home with a plan for outpatient follow-up and investigations. He re-presented to hospital 6 days later with severe fluid overload. Echocardiogram was suggestive of impaired left ventricular systolic function; subsequent cardiac MRI confirmed this and was indicative of a dilated cardiomyopathy. A diagnosis of dilated cardiomyopathy with cardiorenal syndrome was made, most likely secondary to viral myocarditis in view of his initial presentation. He was diuresed and treated with prognostic medications for heart failure. His symptoms resolved and on subsequent outpatient review he was feeling well.